2022
DOI: 10.1038/s41598-022-09958-4
|View full text |Cite|
|
Sign up to set email alerts
|

Decomposing rural–urban differences in successful aging among older Indian adults

Abstract: The modernization and shift towards urbanized lifestyles have triggered several diseases, and the context of aging varies in urban and rural settings in India. The study aimed to investigate the urban–rural differences in successful ageing among older adults in India and the contributing factors in those differences. The study utilizes data from nationally representative Longitudinal Ageing Study in India (LASI, 2017–18). The analytical sample size for the study was 31,464 older adults aged 60 years and above.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 77 publications
3
13
0
2
Order By: Relevance
“…The oldest-older (80 years and above), lower educated, and unemployed individuals are more likely to experience poor health than their counterparts. With increasing age, the risk of both communicable and non-communicable diseases is high, negatively affecting SRH [ 16 ]. Similarly, the lower educated and unemployed are more vulnerable to socio-economic distress, positively associated with poor SRH [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oldest-older (80 years and above), lower educated, and unemployed individuals are more likely to experience poor health than their counterparts. With increasing age, the risk of both communicable and non-communicable diseases is high, negatively affecting SRH [ 16 ]. Similarly, the lower educated and unemployed are more vulnerable to socio-economic distress, positively associated with poor SRH [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies found significant variation in prevalence and predictors of SRH in accordance with the place of residence. A recent study has examined the rural–urban gap in health status among the older population in India using large-scale sample survey data and found significant variation in predictors of successful aging between rural and urban [ 16 ]. However, it hasn't been investigated how the association between marital status and living arrangements with SRH varies depending on the place of residence in India.…”
Section: Introductionmentioning
confidence: 99%
“…Major depression among older adults with symptoms of dysphoria was calculated using the Composite International Diagnostic Interview - Short Form (CIDI-SF) on a scale of 0–10. This scale estimates a probable psychiatric diagnosis of major depression and has been validated in field settings and widely used in population-based health surveys 44 45. It has 10 questions and respondents with positive answers to 3 or more symptoms are considered ‘depressed’.…”
Section: Methodsmentioning
confidence: 99%
“…Aging population across world countries and in low-and middle-income countries in particular poses wide-ranging health, social, and economic challenges, both current and future. India is projected to surpass China as the world's most populous country during 2023 [1] with a Open Access *Correspondence: shobhitsrivastava889@gmail.com International Institute for Population Sciences, Mumbai, Maharashtra, India rapidly growing proportion of older persons that requires improvement of social security and long-term care systems in terms of ensuring a successful aging process [2].…”
Section: Introductionmentioning
confidence: 99%